Brazil : A Century of Change - Pinheiro, Paulo Se´rgio de M. S. (Paulo Se´rgio de Moraes Sarmento); Wilheim, Jorge, 1928-; Sachs, Ignacy (Book collections on Project MUSE., 2009)
Brazil, the largest of the Latin American nations, is fast becoming a potent international economic player as well as a regional power. This English translation of an acclaimed Brazilian anthology provides critical overviews of Brazilian life, history, and culture and insight into Brazil's development over the past century. The distinguished essayists, most of whom are Brazilian, provide expert perspectives on the social, economic, and cultural challenges that face Brazil as it seeks future directions in the age of globalization.All of the contributors connect past, present, and future.